2015
DOI: 10.1111/neup.12265
|View full text |Cite
|
Sign up to set email alerts
|

Nucleostemin promotes the proliferation of human glioma via Wnt/β‐Catenin pathway

Abstract: Nucleostemin, nucleolar guanosine triphosphate (GTP)-binding protein 3, is a member of the MMR1/HSR1 GTP-binding protein family. The important roles of nucleostemin in self-renewal, cell cycle regulation, apoptosis, and cell proliferation of various cancer types as been shown. Nevertheless, its expression and potential functions in human glioma is still unclear. In the present study, we demonstrated that up-regulation of nucleostemin was tightly related to poor 5-year-survival ratios. In serum-starved and re-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
(73 reference statements)
2
9
0
Order By: Relevance
“…These results also indicated that inhibition of ribosome biogenesis might disrupt oncology pathways thus inhibit cell proliferation and promote apoptosis of PTC. This proposition is consistent with the report that neucleolar protein Nucleostemin promoted cell proliferation of human glioma via Wnt/β-Catenin pathway [ 25 ], suggesting abnormal expression of nucleolar protein could active oncology pathway.…”
Section: Discussionsupporting
confidence: 93%
“…These results also indicated that inhibition of ribosome biogenesis might disrupt oncology pathways thus inhibit cell proliferation and promote apoptosis of PTC. This proposition is consistent with the report that neucleolar protein Nucleostemin promoted cell proliferation of human glioma via Wnt/β-Catenin pathway [ 25 ], suggesting abnormal expression of nucleolar protein could active oncology pathway.…”
Section: Discussionsupporting
confidence: 93%
“…These data were also confirmed in Wnt10B knockdown cells, demonstrating that reduced Wnt10B expression also downregulated expression of Oct4 and Nanog in gastric cancer cells in vitro . Further studies may confirm whether Wnt10B knockdown inhibits β-catenin translocation into cell nuclei, as shown by previous studies in other cancers (3538). …”
Section: Discussionsupporting
confidence: 78%
“…However, it is noteworthy that there are inconsistent reports regarding the cell cycle arrest caused by GNL3 dysregulation in different tumor cells. It is demonstrated that GNL3 knockdown triggers cell cycle arrest at the G1 phase in hepatocellular carcinoma HepG2 and Hep3B cells,12 ovarian cancer SKOV-3 cells,13 and glioma U251 and U373MG cells 19. Conversely, Meng et al20 claim that GNL3 knockdown triggers G2-M arrest in U2OS cells, while overexpression of GNL3 is revealed to induce G1 arrest through inhibiting MDM2 in U2OS cells 21.…”
Section: Discussionmentioning
confidence: 99%